KERJASAMA INDONESIA – WINROCK INTERNATIONAL DALAM SUSTAINABLE DEVELOPMENT PROGRAM SUPPORT DI KABUPATEN SIAK - Febriani, Filmia Amanda; Iskandar, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Environmental issues have now become a phenomenon of international concern. Global warming, which is an environmental issue, has become a complex problem, one of the causes of which is the relationship between fires and peatlands. Indonesia, which is the 4th country with the largest peatland area, realizes this problem and is committed to overcoming this problem. Thus, this paper will attempt to answer the question of why Indonesia cooperates with Winrock International in the Sustainable Development Program Support in Siak District. In conducting research, the theory of international cooperation from the perspective of pluralism and a descriptive qualitative approach with primary and secondary data collection techniques have been used. So that it aims to know and understand more deeply the collaboration carried out by the Ministry of Home Affairs - Winrock International in Siak District. The results of the research show that the Ministry of Home Affairs (Indonesia) and Winrock International have similar goals, namely the two partners aim to empower communities in the environmental sector. Furthermore, the existence of environmental problems, land fires related to peatlands in Siak District are part of the cooperation program. This cooperation also received full funding from Winrock International partners. Keywords : Peatland, International Cooperation, Winrock International, Environtmen, Siak District